Benefit of adjuvant chemotherapy in high-risk colon cancer: A 17-year population-based analysis of 6131 patients with Union for International Cancer Control stage II T4N0M0 colon cancer. (September 2020) - Teufel, Andreas; Gerken, Michael; Fürst, Alois; Ebert, Matthias; Hohenthanner, Ina; Klinkhammer-Schalke, Monika
Abstract: Background: The benefit of adjuvant chemotherapy in Union for International Cancer Control (UICC) stage III colon cancer has been demonstrated in numerous studies. While adjuvant chemotherapy is generally not recommended in stage II patients, its role in high-risk UICC stage II disease (e.g. T4 tumours) remains controversial. Methods: The present population-based multicenter cohort study investigated the influence of adjuvant chemotherapy on survival and recurrence rates in high-risk UICC stage II T4N0M0 tumours. Based on an anonymised nationwide ADT data set from 31 clinical cancer registries, we identified a total of 6651 patients with a T4 tumour of the colon, of whom 6131 were eligible for survival analysis. A matched-pair analysis based on propensity scores (PSM) was performed with a subset of 3986 patients. Results: Multivariable analyses demonstrated a significant benefit of adjuvant chemotherapy for overall survival (OS) (hazard ratio [HR]: 0.711, 95% confidence interval [CI]: 0.643–0.785, p  < 0.001), cumulative recurrence rate (HR: 0.780, 95% CI: 0.681–0.893, p  < 0.001), and recurrence-free survival (HR: 0.715, 95% CI: 0.652–0.785, p  < 0.001) further confirmed by the matched-pair cohort. Conclusion: This large and representative study demonstrated a significant advantage of adjuvant chemotherapy for patients with T4 UICC stage II colon cancer in terms of OS, recurrence rate, and relapse-free survival. Based on these results, adjuvant chemotherapy should be recommended for these patients. Highlights: What is already known about this subject? ·Adjuvant chemotherapy is generally not recommended in stage II patients. Administration of adjuvant chemotherapy in high-risk UICC stage II disease (e.g., T4 tumors) remains controversial. Robust data supporting adjuvant chemotherapy in high-risk UICC stage II disease (e.g., T4 tumors) are lacking. What are the new findings? We demonstrated a markedly prolonged overall survival in subjects who received adjuvant chemotherapy. We demonstrated a highly significant improvement in relapse-free survival achieved by adjuvant chemotherapy. Our analysis was performed on large registry data. How might it impact on clinical practice in the foreseeable future? Our findings will change current clinical practice, because based on our results, adjuvant chemotherapy should generally be recommended for T4 UICC stage II colon cancer patients.